2-alkylaminoethyl-1,1-bisphosphonic acids are potent inhibitors of the enzymatic activity of Trypanosoma cruzi squalene synthase - Rodrígues-Poveda, C.A. (2012)
As part of our efforts aimed at searching for new antiparasitic agents, the effect of representative 2-alkylaminoethyl-1,1-bisphosphonic acids on Trypanosoma cruzi squalene synthase (TcSQS) was investigated. These compounds had proven to be potent inhibitors of T. cruzi. This cellular activity had been associated with an inhibition of the enzymatic activity of T. cruzi farnesyl diphosphate synthase. 2-Alkylaminoethyl-1,1-bisphosphonic acids appear to have a dual action, since they also inhibit TcSQS at the nanomolar range. Copyright © 2012, American Society for Microbiology. All Rights Reserved.